Extraction of hysteretic properties of seismically isolated bridges from quick release field tests. - Chen, Qingben (Earthquake engineering & structural dynamics.)
A simple procedure for identifying hysteretic properties of seismically isolated bridges from full scale quick release tests is presented in this paper. An analytical solution for the quick release response of a SDOF system with a bilinear spring is derived. Based on the solution, some characteristics of such systems are obtained. A time domain optimization method is employed to identify the hysteretic properties of the lead rubber are expressed as a combination of the rate independent (hysteretic) damping and the linear viscous damping. The Menegotto-Pinto (MP) model and bilinear model are used to represent the force displacement relation of the lead rubber bearings. In both the longitudinal and transverse directions the bridges have been idealized as single degree of freedom (SDOF) systems. Time histories recorded from the field quick release tests on two bridges are used for the examples presented herein. The hysteretic loops of the isolators obtained from laboratory tests are compared with those obtained using the optimization method, and they agree well. In conclusion, the procedure shown in this paper can be used to identify the essential in situ hysteretic characteristics of isolation bearings from quick release field testing.